Optical and thermal properties of neodymium doped tellurite nanostructured glass - Mat Jan, Nur Amanina (2014)
Neodymium doped tellurite nanostructured glass having a composition of (75-x)TeO2-15MgO-10Na2O-(x)Nd2O3, where 0 = x = 2.5 mol% has successfully been prepared by melt-quenching technique. The amorphous nature of the glass was confirmed from the X-ray diffraction pattern. Thermal parameter of the glass was analyzed by using differential thermal analysis. It was found that the glass exhibits the transition temperature between 255 - 259 oC, crystallization temperature between 428 to 450 oC and melting temperature from 505 to 549 oC. The nanoparticles were obtained by applying heat treatment to the glass at near crystallisation temperature of 460 oC for 30 minutes. The existence of nanocrystalline nature of this glass was confirmed by X-ray diffraction and transmission electron microscopy. The vibrational study was conducted using Fourier transform infrared spectroscopy in the range 4000 - 400 cm-1. It was found that there were three absorption peaks around 687 - 712 cm-1, 624 - 632 cm-1 and 467 - 474 cm-1 which are due to the stretching of Te-O bending in TeO3 trigonal pyramidal (tp) units, Te-O bands stretching vibration in TeO4 trigonal bipyramidal (tbp) units and the bending vibrations of Te-O-Te or OTe- O linkages, respectively. The optical absorption behaviour was studied using UVVisible spectrophotometer. The values of indirect optical band gap are in the range 3.15 - 3.22 eV and for direct band gap the values are in the range 3.37 - 3.43 eV. The Urbach energy value for glass system was found to be in range 0.208 eV and 0.125 eV. The emission spectrum was recorded using photoluminescence spectrometer. The fluorescence spectra of Nd3+ ions exhibit emission transition of 2P1/2?4I9/2, 2D3/2?4I9/2 and 4G7/2?4I9/2 under 585 nm excitation wavelengths. It was found that the intensity is enhanced in the heat-treated glass compared to those of prepared glass.